Optimalisasi Penyusunan Dokumentasi Asuhan Keperawatan bagi Perawat Kalimantan Barat: Optimizing the Preparation of Nursing Care Documentation for West Kalimantan Nurses - Nita Arisanti Yulanda; Mita Mita; Ichsan Budiharto; Ratih Sulistianingrum; Arizki Rahman Hakim; Kharisma Aji Martadi; Rosaldi Millenianto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Nursing is a profession for health workers to maintain the quality of health services. The nursing profession makes efforts to develop professional service quality, one of which is regarding nursing care standards, namely documentation. Quality documentation is handy for hospitals in increasing accreditation, communication between professions, indicators of quality services, and a research facility. Nursing documentation, one of them is that diagnosis is an essential aspect of nursing practice. Standard Diagnosis Keperawatan Indonesia, Standart Luaran Keperawatan Indonesia, and Standard Intervensi Keperawatan Indonesia have been compiled by the PPNI professional organization and are expected to improve the quality of Indonesian nursing care documentation. Therefore, there is a need for comprehensive socialization for nurses; the activities carried out were attended by 210 nurses and conducted virtually through zoom meetings. During the activity, pretest and posttest were carried out to determine participants' level of knowledge about SDKI. From the results of the tabulation of participants, it was found that most of the participants were educated professional nurses (70%) and primary nurses (51.90%). The results of the analysis of the results of the pretest-posttest obtained a p-value = 0.000, which indicates a significant difference in nurses' knowledge. The results of this pretest-posttest show that nurses' knowledge can be increased by providing socialization of nursing diagnosis standards. It is expected that hospitals can routinely provide knowledge stimulation, especially about nursing care documentation.